2018
DOI: 10.1007/s00270-018-1995-z
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Radiology and Spanish Medical Students: A Survey of Knowledge and Interests in Preclinical and Clinical Courses

Abstract: This study demonstrates that medical students in our University have poor knowledge of IR; however, they are overwhelmingly positive in their desire to have this subject taught as distinct curriculum in medical school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
3
12
0
4
Order By: Relevance
“…Despite the local character of this survey, this could be a representation of sparce opportunities to be exposed in such modules. Similar findings were reported by a Spanish survey, which underlined that local medical students had limited exposure to and knowledge of IR; of which 98% of clinical and 100% of preclinical students would like to be exposed to IR in their curriculum [30]. Similar findings were reported from a recent Australian cross-sectional survey [31].…”
Section: Discussionsupporting
confidence: 84%
“…Despite the local character of this survey, this could be a representation of sparce opportunities to be exposed in such modules. Similar findings were reported by a Spanish survey, which underlined that local medical students had limited exposure to and knowledge of IR; of which 98% of clinical and 100% of preclinical students would like to be exposed to IR in their curriculum [30]. Similar findings were reported from a recent Australian cross-sectional survey [31].…”
Section: Discussionsupporting
confidence: 84%
“…However, due to only recent accreditation of IR as a sub-specialty, modules for IR based teaching have not been amalgamated into undergraduate medical curriculum. In several studies across different countries, medical students have demonstrated a poor understanding of IR, owing to suboptimal teaching and exposure levels (O'Malley and Athreya 2012; Atiiga et al 2017;de Gregorio et al 2018;Commander et al 2014;Leong et al 2009;Ghatan et al 2010;Nissim et al 2013;Foo et al 2018;Ojha et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…O crescimento da RI nas diferentes áreas médicas e suas aplicações clínicas tem se mostrado exponencial nos últimos anos 1,2,[5][6][7] . Contudo, problemas como a falta de reconhecimento dasubespecialidade e a dificuldade na diferenciação com a radiologia diagnóstica são frequentes e desafiadores [1][2][3] . A precária relação da RI com a população médica e acadêmica já foi evidenciada em países como Estados Unidos, Espanha e Irlanda 1,8 .…”
Section: Discussionunclassified
“…Estudo anterior observou que a introdução da RI durante a graduação era mais forte nas universidades que possuíam radiologistas intervencionistas como professores titulares. Os entrevistados consideraram que os treinamentos em RI deveriam ser uma mistura de radiologia e cirurgia, o que já foi proposto e realizado com resultados satisfatórios em outras universidades 1,12,15 .…”
Section: Discussionunclassified
See 1 more Smart Citation